DESTINATION HOSPITALITY SERVICE DELIVERY CAPABILITY AND MARKETING PERFORMANCE OF TOURIST SITES: EVIDENCE FROM SOUTH-SOUTH NIGERIA - Joseph Sunday Etuk (American Journals, 2022)
The South-South geo-political zone of Nigeria has been identified as one of the regions characterized by low tourism patronage despites her huge natural and cultural attraction assets/opportunities and perceived hospitable disposition of her people. Therefore, this study was carried out to empirically ascertain destination hospitality service delivery capability and marketing performance of tourist sites Akwa-Ibom State, South-South Nigeria in terms of tourists’ satisfaction and revisit intention. To carry out the study, a survey method was adopted whereby primary data were obtained from 308 respondents through the questionnaire method. Descriptive and univariate analysis was done using simple percentages, mean score, standard deviation while the Pearson Product Moment Correlation technique was deployed for hypotheses testing. The analyzed data revealed that destination hospitality service delivery was strongly and positively correlated with tourists’ satisfaction, but the correlation with revisit intention to the tourist sites was insignificant. The study concluded that although tourists were not impressed by the hospitality services delivery by hospitality organizations operating around the tourist sites in Akwa-Ibom, they, however, expressed willingness to return to the sites in the future. The study, therefore recommended the provision of adequate and high-quality hotel and restaurant facilities by entrepreneurs for visitors’ fun and relaxation and business sustainability.
Keywords: Destination hospitality service delivery capability, destination marketing performance